1986
DOI: 10.1080/00288233.1986.10430457
|View full text |Cite
|
Sign up to set email alerts
|

Pasture utilisation in hill country 2. A general model describing pasture mass and intake under sheep and cattle grazing

Abstract: A general model describing daily changes in pasture mass and apparent individual herbage intake under mob grazing was developed for future use as a component of feed budgeting within hill country farming systems. The basic concept of the model is that of a negative exponential. The exponent includes animal density, time, and a constant k -the relative rate of pasture disappearance. Where k is unknown, the model is useful in a historical sense for describing pasture mass and intake levels at intermediate stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As a consequence, he suggested that management practices should aim to provide the maximum amount of live tissues with high digestibility to animals, particularly leaves, as a means of increasing intake and performance. This idea led to the concept of green dry matter allowance [60], which evolved to leaf dry matter allowance. These practices were effective in providing a good fit between herbage allowance and animal performance data (as originally reported by Mott [31]) in relation to the traditional asymptotic curve [61], but magnified the problem of excessive herbage mass with high proportions of stems and dead material, with negative implications on herbage and animal production.…”
Section: Forage Grass Research-a Historical Overviewmentioning
confidence: 99%
“…As a consequence, he suggested that management practices should aim to provide the maximum amount of live tissues with high digestibility to animals, particularly leaves, as a means of increasing intake and performance. This idea led to the concept of green dry matter allowance [60], which evolved to leaf dry matter allowance. These practices were effective in providing a good fit between herbage allowance and animal performance data (as originally reported by Mott [31]) in relation to the traditional asymptotic curve [61], but magnified the problem of excessive herbage mass with high proportions of stems and dead material, with negative implications on herbage and animal production.…”
Section: Forage Grass Research-a Historical Overviewmentioning
confidence: 99%